Advancing Sustainable Practices: Integrated Pedological Characterization and Suitability Assessment for Enhanced Irish Potato Production in Tsangano and Angónia Districts of Tete Province, Mozambique - Tamara José Sande; Balthazar Michael Msanya; Hamisi Juma Tindwa; Alessandra Mayumi Tokura Alovisi; Johnson M. Semoka; Mawazo Shitindi (Soil Systems, 2025)
Irish potato (Solanum tuberosum) is a critical crop for food security and economic growth in Tsangano and Angónia Districts, Central Mozambique. Challenges like inconsistent yields and variable quality are often linked to suboptimal soil conditions, which limit production. This study aimed to classify and evaluate the suitability of soils for potato cultivation in Tete Province, where detailed soil assessments remain limited. Four pedons—TSA-P01 and TSA-P02 in Tsangano and ANGO-P01 and ANGO-P02 in Angónia—were examined for bulk density, texture, pH, organic carbon, and nutrient content using a combination of pedological methods and laboratory soil analysis. To determine each site’s potential for growing Irish potatoes, these factors were compared to predetermined land suitability standards. The pedons were very deep (>150 cm) and had textures ranging from sandy clay loam to sandy loam. TSA-P02 had the lowest bulk density (0.78 Mg m−3) and the highest available water capacity (182.0 mm m−1). The soil pH ranged from 5.6 to 7.9, indicating neutral to slightly acidic conditions. Nutrient analysis revealed low total nitrogen (0.12–0.22%), varying soil organic carbon (0.16–2.73%), and cation exchange capacity (10.1–11.33 cmol(+) kg−1). Pedons TSA-P01, ANGO-P1, and ANGO-P02 were characterized by eluviation and illuviation as dominant pedogenic processes, while in pedon TSA-P02, shrinking and swelling were the dominant pedogenic processes. Weathering indices identified ANGO-P01 as most highly weathered, while TSA-P02 was least weathered and had better fertility indicators. According to USDA Taxonomy, the soils were classified as Ultisols, Vertisols, and Alfisols, corresponding to Acrisols, Alisols, Vertisols, and Luvisols in the WRB for Soil Resources. All studied soils were marginally suitable for potato production (S3f) due to dominant fertility constraints, but with varying minor limitations in climate, topography, and soil physical properties. The findings hence recommended targeted soil fertility management to enhance productivity and sustainability in potato cultivation.